2017
DOI: 10.3390/app7070647
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Efficiency of Compartmented Alginate Fibres Encapsulating a Rejuvenator as an Asphalt Pavement Healing System

Abstract: This paper explores the potential methods for evaluating a healing system for asphalt pavements. The healing system under investigation involves compartmented calcium-alginate fibres encapsulating an asphalt binder healing agent (rejuvenator). This system presents a novel method of incorporating rejuvenators into asphalt pavement mixtures. The compartmented fibres are used to distribute the rejuvenator throughout the pavement mixture, thereby overcoming some of the problems associated with alternate asphalt pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…Tabaković et al further demonstrated that optimum healing time for zeer open asfalt beton (ZOAB) mix using compartmented alginate fibers encapsulating rejuvenator is 20 h. Figure illustrates successful crack closure (healing) in an asphalt test specimen containing 5% compartmented alginate fibers encapsulating the rejuvenator after 20 h of healing.…”
Section: Embedded Rejuvenation Encapsulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Tabaković et al further demonstrated that optimum healing time for zeer open asfalt beton (ZOAB) mix using compartmented alginate fibers encapsulating rejuvenator is 20 h. Figure illustrates successful crack closure (healing) in an asphalt test specimen containing 5% compartmented alginate fibers encapsulating the rejuvenator after 20 h of healing.…”
Section: Embedded Rejuvenation Encapsulationmentioning
confidence: 99%
“…Figure shows the crack propagation speed within semi‐circular bend (SCB) test sample at the initial test and after two healing stages . It is clear from the graph that the fiber mix experiences slower crack propagation.…”
Section: Embedded Rejuvenation Encapsulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The moisture susceptibility of the mixtures studied was evaluated by moisture indices using Marshall Stability Ratio (MSR) for different kinds of specimens following ASTM D1559 standard method. The MSR was calculated according to Equation (1).…”
Section: Moisture Susceptibility Testmentioning
confidence: 99%
“…Asphalt concrete is a self-healing material which can close micro cracks during rest periods through bitumen flow and diffusion [1]. The potential benefits of applying self healing technology to asphalt pavements include reduced road maintenance with a subsequent reduction in CO 2 production, improved safety for both road users and road workers, improved road life span, and reduced cost of road maintenance [2].…”
Section: Introductionmentioning
confidence: 99%